Vulvar leukoplakia: therapeutic options - Yordanov, Angel; Tantchev, Latchezar; Kostov, Stoyan; Slavchev, Stanislav; Strashilov, Strahil; Vasileva, Polina (Menopause Review/Przegląd Menopauzalny, 2020)
Vulvar leukoplakia is not a histological diagnosis and involves several diseases. Most commonly, these are vulvar lichen sclerosus and squamous cell hyperplasia of the vulva. These two conditions have similar aetiology, clinical presentation and treatment but different histopathological changes. They both lead to significant impairment of quality of life, risk of malignancy, as well as recurrence after treatment. Treatment of these conditions includes topical corticosteroids as a first-line therapy, but they have their side effects and not all patients are receptive to this therapy. This requires the use of alternative therapeutic options such as topical calcineurin inhibitors, topical and systemic retinoids, other steroid creams, various destructive techniques and, as a last resort, surgical removal of affected tissues. Surgical treatment should be avoided, despite the malignant potential, because of recurrence risk in both diseases New therapeutic approaches are coming into effect in gynaecological practice due to potential risks of the above-mentioned methods. Platelet-rich plasma therapy, ablative and non-ablative laser treatment, and new topical medicines, are some of the new options applied to improve the efficacy of treatment avoiding the side effects of conventional medications. A number of them are still in their initial phase of application and time will tell their effectiveness.